(NsLXOZI ZASTIGLIJ SAMOCW)QÆT(B. (NsERÆQ LISTÆWOK DO SOROKOWIN PISXMENNICÆ(B, (NVURNALÆSTKI Æ NAUKOWICÆ qROSLAWI mELXNI^UK (B/s)E - (NmELXNI^UK(B, (Nb(B. )Qæ.s)E ((NbOGDAN )QæWANOWI^(B)s)E; (NwASKAN(B, (Nw(B. (Nw(B.s ((NwASILX wASILXOWI^(B)s; (NgRIGOR^UK(B-(NwOJTKO(B, (Nn(B. (Nw(B.s ((NnATAL)QÆQ wOLODIMIRÆWNA(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s; (NdOWBU[(B, (No(B. )Qæ.s)E ((NoLEKSANDR )QæWANOWI^(B)s)E; (NmELXNIK(B, (Ng(B. (Nt(B.s ((NgALINA tERENT)QÆÇWNA(B)s)E; (NpARA]UK(B, (Ns(B. (No(B.s ((NsERG)QÆJ oLEKSANDROWI^(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2023)
(Nu WIDAWNICTW)QÆ (B"(NrODOWÆD(B" (NWIJ[LA W SWÆT ^ERGOWA SERÆQ LISTÆWOK(B. "(NsLXOZI ZASTIGLIJ SAMOCWÆT(B. (NsERÆQ LISTÆWOK DO SOROKOWIN PISXMENNICÆ(B, (NVURNALÆSTKI Æ NAUKOWICÆ qROSLAWI mELXNI^UK(B". (NbUKOWINSXKÆ POETI wASILX wASKAN(B, (NoLEKSANDR dOWBU[(B, (NgALINA mELXNIK TA ÆN[Æ W[ANUWALI PAM(B'(NQTX ^UDOWOÇ L@DINI(B, (NVURNALÆSTKI(B, (NDOCENTKI ~ERNÆWECXKOGO NACÆONALXNOGO UNÆWERSITETU ÆM(B. (N`(B. (NfEDXKOWI^A (B, (NGROMADSXKOÇ DÆQ^KI qROSLAWI mELXNI^UK(B. (NsWO@ PRISWQTU (B"(NnAD KOLISKO@ DONXKI(B" (NNAPISAW TAKOV BATXKO qROSLAWI mELXNI^UK bOGDAN mELXNI^UK(B.s)E
(NpRO)QÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNIs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E